STUDI PENERAPAN AUDIT INTERNAL PEMBERIAN KREDIT PADA PT BANK TABUNGAN NEGARA (PERSERO) CABANG BENGKULU - Yetti Afrida Indra (Jurnal Bisnis dan Ekonomi, 2016)
Credit is one of the businesses that are important to the world of banking and credit will contribute considerable revenue, butbehind it was the management of credit have various problems are quite complicated. In this complex credit management, itwould require an independent appraisal function of internal audit.With the existence of adequate internal audit, expected anyerrors, irregularities, fraud, and others that hurt the company can be kept to a minimum. The authors conducted a study atPT.BTN (Persero) Branch Bengkulu, Bengkulu S. Parman road. The research was conducted from January to finish. Object ofresearch is the study of the implementation of internal audit of credit. The purpose of this study was conducted to determine theadequacy of the implementation of internal audit provision of credit at PT.BTN (Persero) Branch Bengkulu.The method of research used analytical descriptive method the authors were with the case study approach, whereas to obtainthe data in the form of interviews conducted field research,quesioner and documentation. It also conduc ted the researchliterature. From the results of research conducted can be seen that the activities and the activities of credit at PT.BTN (persero)Branch Bengkulu increasingly broad and complex, while the author looks at the current internal audit staff is still lacking. Butviewed from the position of internal auditing is an independent and competent, the internal audit program, the stages ofimplementation of internal audit, internal audit reports and follow-up of internal audit, credit based on the principle 5C, theprocedures for granting credit assistance, and the rate of return credit, it can be concluded that the implementation of internalaudit lending PT.BTN (Persero) is adequate. It can be seen from the hypothesis that the writer suggested, namely internal auditof credit have been implemented adequately, is acceptable.Keywords : internal audit, credit, analytical descriptif